Impedance spectroscopy and conduction mechanism of ferroelectric rich PbZr0.52Ti0.48O3−CoFe2O4 magnetoelectric composite. Issue 13 (September 2020) - Ahmed, S.; Atif, M.; Nadeem, M.; Ali, Z.; Khalid, W.; Nasir Khan, M.
Abstract: In the present work, structural and dielectric properties of 0.7 P b Z r 0.52 T i 0.48 O 3 − 0.3 C o F e 2 O 4 composite prepared by a mixed oxides route were explored. X-ray diffraction analyses confirmed the formation of distinct C o F e 2 O 4 and P b Z r 0.52 T i 0.48 O 3 phases in the prepared composite. Temperature dependent dielectric permittivity behavior displayed three distinct peaks: a frequency independent peak at high temperature (T = 663K) is identified as structural phase transition of P b Z r 0.52 T i 0.48 O 3 and two thermally activated frequency dependent peaks which showed a Debye- and relaxor-like behaviors at low and intermediate temperatures, respectively. The mechanism for these relaxations is elucidated on the basis of conduction associated with the single- and doubly-ionized oxygen vacancies. Impedance spectroscopy analysis was used to estimate the activation energy ( E a ) of constituent phases and we found that P b ( Z r 0.52 T i 0.48 ) O 3 phase has a dominant role (i.e., E P Z T > E C F O ) in describing the relaxation/conduction mechanism of prepared composite. Moreover, the values of E a calculated from the dielectric, impedance and conductivity data were found to be comparable which clearly indicate that the relaxation and conduction processes in the prepared composite are related to same origin.